Physiological and metabolic analyses reveal the proline-mediated flowering delay mechanism in Prunus persica - Park, Yeonju; Muthuramalingam, Pandiyan; Jeong, Jae Hoon; Kim, Seung Heui; Shin, Hyunsuk (Frontiers in Plant Science, 2024)
Peaches are susceptible to various environmental stresses. Particularly in late spring, freezing temperatures can damage peaches and consequently impact their productivity. Considering this issue, flowering delay is one of the prominent strategies to avoid spring frost damage.Our previous study confirmed that treatment with 5% sodium alginate + 100 mM CaCl2 (5AG) to avoid frost damage in the blooming stage delays flowering. To reveal the flowering delay mechanism of peach, this study systematically analyzed the modification of amino acid profiles in control and 5AG-treated peach plants at different day intervals. Our findings indicated that arginine (Arg), glutamate (Glu), and proline (Pro) levels differed between control and 5AG-treated peach shoots throughout the phenological development of flower buds. Furthermore, two amino acids (Arg and Glu) are involved in the Pro pathway. Thus, using a computational metabolomics method, Pro biosynthesis and its characteristics, gene ontology, gene synteny, cis-regulatory elements, and gene organizations were examined in order to decipher potential Pro metabolism involvement in the peach flowering delay. In addition, qRT-PCR analysis showed the transcriptional regulation of Pro related and flowering-responsive genes and their role in flowering delay. Overall, this pilot study provides new insights into the role of Pro in flowering delay mechanisms in Prunus persica through 5AG treatment.